Professional pressures in physical education and sports professors in light of certain variables. - Boussag, Badreddine (sports creativity, 2024)
The study aimed to identify the professional pressures in the professors of physical education and sports in the light of some variables, as well as to know the level of professional pressures in professors of physical education and sports, and the study sample consisted of (35) professor of physical education and sports at the intermediate stage of Education .the researcher took the analytical descriptive approach, which is because it is best suited in such studies, as for the study tools, the necessary data was collected using a professional pressure scale of 36 phrases, spread across six dimensions. he used a triple step Licert scale (Always, Sometimes, Never), and the scale constant coefficient (0.93) was reached and applied to the study sample , and the researcher relied on the statistical package program SPSS, the results of the study include: The level of professional stress among physical education and sports teachers is average and the presence of statistically significant differences between the study sample in the pressure level of Professional Teachers of physical education and sports according to the variables of ), social status,seniority in teaching(.